1. Jahresbericht des Instituts für Organisationsökonomik - Alexander Dilger; Stephanie Kiefer; Katrin Scharfenkamp (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2011)
Dieser Jahresbericht informiert über das Institut für Organisationsökonomik im Wintersemester 2010/2011 und Sommersemester 2011. Zuerst werden das Institut für Organisationsökonomik, seine Professoren und Mitarbeiter vorgestellt. Danach wird über die Forschung, Lehre und Weiteres des Instituts berichtet. – – This annual report informs about the Institute for Organisational Economics in the winter semester 2010/2011 and the summer semester 2011. First the Institute for Organisational Economics, its professors and employees are introduced. Then it reports on research, teaching and furhter activities of the institute.
Keywords: 330